TUAN GURU ANTARA IDEALITAS NORMATIF DENGAN REALITAS SOSIAL PADA MASYARAKAT LOMBOK - Fahrurrozi, Fahrurrozi (JURNAL PENELITIAN KEISLAMAN, 2010)
Shifting paradigm and social labeling towards tuan guru in Lombok have commonly led to ambiguity and overlap. This is mainly caused by varied contributing factors such as social and religious status, knowledge, attitudes, teaching activity in Islamic boarding schools, preaching activities that one engage. Even political interest contribute to the changing predicate of tuan guru that is labeled to someone. As a result, this sacred social and religious predicate widens and may be used by one who has ideally not reached the status. No wonder, there are lots of tuan gurus. Considering this phenomena, this research aims at decribing normative discourse of the predicate of tuan guru and then to look at how this discourse is empirically debated among Sasaknese. The research employs sociological approach and uses inductivedescriptive analysis. The researh shows that one who has a predicate as a tuan guru should have deep knowledge, individual and social piety, charisma and is socialy accepted. This predicate also requires that one have performed pilgrimage, be able to read Islamic classical books, posses Islamic educational institution, and have a high social commitment to the society.